2014
DOI: 10.1002/pssb.201451092
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic exploration of vacancy centres with the Jahn-Teller effect. Application to the ZnSe crystal

Abstract: We show that the structure, properties, and concentration of vacancies in crystals can be studied by ultrasonic experiments previously employed for impurity centres only. Measurements of the temperature dependence of attenuation and phase velocities of ultrasonic shear waves of 52 MHz propagating along the crystallographic axis [110] of nominally pure ZnSe single crystals (grown by the seeded physical vapour transport method) show strong anomalies which are typical for relaxation processes in system with isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
6
0
4
Order By: Relevance
“…The obtained in this way possible values ofhω τ and relatedhω e , K T , and K E (ω e = K E /M ) are listed in Table I together with the stabilization energies of the tetragonal and trigonal extrema points, calculated by Eqs. (7) and (8). Next, we note that the attenuation peak of the ultrasonic wave coupled with the c T elastic modulus is by almost an order of magnitude larger than for the wave coupled with the c E modulus (Fig.…”
Section: Extrema Points On the Six-dimensional Apesmentioning
confidence: 72%
See 1 more Smart Citation
“…The obtained in this way possible values ofhω τ and relatedhω e , K T , and K E (ω e = K E /M ) are listed in Table I together with the stabilization energies of the tetragonal and trigonal extrema points, calculated by Eqs. (7) and (8). Next, we note that the attenuation peak of the ultrasonic wave coupled with the c T elastic modulus is by almost an order of magnitude larger than for the wave coupled with the c E modulus (Fig.…”
Section: Extrema Points On the Six-dimensional Apesmentioning
confidence: 72%
“…Along with traditional methods of investigation of electronic structure, dynamics and local symmetry of crystal dopants and other active centers in polyatomic systems by means of experimental electron spin resonance (ESR) and pulse techniques using electron spin echo (ESE, ES-EEM spectroscopy) [1][2][3][4] , recent studies of II-VI:3d and III-V:3d crystals by means of ultrasonic experiments demonstrated the efficiency of this novel approach in obtaining important information about the structure and properties of Jahn-Teller effect (JTE) centers in such crystals [5][6][7][8] . Ultrasonic experiments are uniquely suited for investigation of JTE problems because the interaction of the ultrasound wave of strain produces characteristic anomalies in speed, relaxation, and attenuation when its direction of propagation and polarization coincides with the direction of JTE distortions.…”
Section: Introductionmentioning
confidence: 99%
“…Почти все примесные центры в кристаллах подвержены эффекту Яна−Теллера (ЭЯТ) в основном или возбужденном состоянии. Недавние исследования полупроводниковых кристаллов, содержащих 3d-примеси с ЭЯТ, показали эффективность ультразвуковых экспериментов в получении существенной информации о структуре и свойствах таких центров [1][2][3][4][5]. В зависимости от направления распространения деформационной волны ультразвука через центр с ЭЯТ, эквивалентные минимумы его адиабатической поверхности потенциальной энергии (ППЭ) становятся неэквивалентными, что непосредственно сказывается на измеряемых температурной и частотной зависимостях поглощения и скорости ультразвука и проявляется в виде характерных аномалий.…”
Section: Introductionunclassified
“…В зависимости от направления распространения деформационной волны ультразвука через центр с ЭЯТ, эквивалентные минимумы его адиабатической поверхности потенциальной энергии (ППЭ) становятся неэквивалентными, что непосредственно сказывается на измеряемых температурной и частотной зависимостях поглощения и скорости ультразвука и проявляется в виде характерных аномалий. Это позволяет определить из ультразвукового эксперимента характер искажений в центрах с ЭЯТ и другие параметры ППЭ примесного центра [2][3][4][5].…”
Section: Introductionunclassified
See 1 more Smart Citation